The Olympic Games: A Social Science Perspective: Second Edition - Toohey, Kristine (CABI, 2014)
The first edition of this book arose as a result of the decision of the International Olympic Committee, in September 1993, to award the Games of the XXVII Olympiad to Sydney, Australia. The announcement prompted us to develop undergraduate and postgraduate courses on the Olympic Games in the School of Leisure, Sport and Tourism at the University of Technology, Sydney (UTS). A considerable amount of research and teaching activity was subsequently developed at UTS, on the Olympic Games generally and on Sydney 2000 specifically. A book seemed a natural progression and it was published in early 2000. Despite the controversies which enveloped the International Olympic Committee in 1998/99, there is no sign of the Olympic Games fading in terms of their sporting, cultural and economic significance. From their origins in ancient Greece, during their revival at the end of the nineteenth century and through most of their twentieth and twenty-first century existence, the Olympic Games have been more than just another sporting event. There is, consequently, an enormous and varied literature available on the Olympic Games. In the mid-1990s we noted that there was, however, no up-todate publication which sought to provide a broad, independent, multi-disciplinary account and analysis of the Olympic phenomenon. This book was designed to fill that gap in the literature.